MANAGEMENT EDUCATION - BEYOND THE CURRICULUM - Y, Dr. Poornima, (IJRDO - Journal of Business Management, 2021)
“It is not the strongest of the species that survives, not most intelligent that survives, it is the one that is the most adaptable to change”- Charles Darwin (1809-1882)The changing scenario of the present Management Education offers students more openings, greater self-confidence and out of the box ways to hone their skills. It includes internationalization with increased focus on international partnerships, international internships, student exchange programs, joint degrees and many other things.  The use of new technologies in Management teaching is a trend that is catching up fast. Greater usage of social media to reach the students is on the rise. The era of persuasive technology has significant implications for higher education and especially in Management Education. It is said that “Technology allows students to become much more engaged in constructing their own knowledge, and cognitive studies show that ability is key to learning success”. This is followed by offering more interdisciplinary programs to the students in the classes and to stimulate them to arrive at solutions in critical situations through team work is in vogue.